Knowledge, Attitude and Practice Towards Exclusive Breast Feeding Among Inhabitants of Ginjo Guduru Kebele, Jimma Town, Oromia Region, Ethiopia - Gebresenbet, Habtamu (International Journal of Child Health and Nutrition, 2020)
Appropriate feeding practices are fundamental importance for the survival, growth, development and health of the infant and young children. However; exclusive breastfeeding remains a challenge because of many factors. It was suggested that mother’s knowledge, attitude and practice determines the effectiveness of exclusive breastfeeding. This research is a cross-sectional study aimed to assesses mother’s knowledge, attitude and practice towards optimal breastfeeding among Ginjo Guduru kebele. The survey was conducted from June 29-July30, 2018, from a total of 315 mothers who had children under one (1) year age, 190 mothers were selected using simple random sampling. Structured pre-tested questionnaires, as well as the in-depth interview, was used to collect the data on the socio-economic, demographic characteristics, knowledge attitude and practice towards exclusive breastfeeding. Among mothers studied about 73.94% had good knowledge of effective breastfeeding, 63.99% of mothers had a positive attitude on effective breastfeeding, and 69.69% had a good practice of effective breastfeeding. About 24.06% of mothers had poor knowledge of effective breastfeeding, approximately 36.11% of mothers had a poor level of attitude on effective breastfeeding, and about 31.31% of mothers had a poor practice of effective breastfeeding. Health service delivery staffs Policymakers, administrators and Non-governmental organisation collaborates to draw strategies to enhance the awareness of mothers about effective breastfeeding.